Characteristic Epithelium with Low‐Grade Atypia Appears on the Surface of Gastric Cancer after Successful Helicobacter pylori Eradication Therapy. Issue 4 (28th April 2014) - Kitamura, Yoko; Ito, Masanori; Matsuo, Taiji; Boda, Tomoyuki; Oka, Shiro; Yoshihara, Masaharu; Tanaka, Shinji; Chayama, Kazuaki
Abstract Background The incidence of gastric cancer after successful Helicobacter pylori eradication has been increasing. We previously reported that epithelium with low‐grade atypia (ELA) appeared on the surface of gastric cancer after H. pylori eradication. Here, we investigate the clinical and biological characteristics of such ELA. Methods We studied 27 cases of gastric cancer detected after successful H. pylori eradication therapy. We examined the prevalence of ELA among these cases and its significance for endoscopic discovery after H. pylori eradication. We additionally investigated the mucus, p53 and Ki67 expressions in ELA. Results Epithelium with low‐grade atypia that continuous with the gastric tumor was detected in 22 of 27 cases (81%), a significantly greater percentage than that for controls (p < 0.01). We found that gastric‐type mucin was frequently expressed in this epithelium. Neither p53‐ nor Ki67‐positive cells were found in ELA, irrespective of their expression in tumor tissue. The presence of ELA was positively correlated with the clinical interval between H. pylori eradication and gastric cancer detection. Conclusions Epithelium with low‐grade atypia on gastric cancer tissue, which may develop from gastric cancer cells, is frequently present after successful eradication therapy. This phenomenon could influence the practice of endoscopic diagnosis of gastric cancers.